"in dem moment wo ich es dann erkenne dann ist es auch gleich wieder weg" – Salienzeffekte in der Sprachperzeption - Anders, Christina Ada; Palliwoda, Nicole; Schröder, Saskia (Linguistik Online, 2014)
In context of the first study on folk linguistic concepts in the German language area carried out by the Kiel DFG research project "perceptual dialectology", this article looks at how salient features could be surveyed and categorized by a stimulus-response-test. After a definition of salience, the study design including the stimulus-response-test is presented. The test was created and modified during the project as a guessing game by the Institute for German Language (IDS Mannheim). The central question in this article is which linguistic features stimulate the informants to locate a speech sample on a map with predetermined cities and hence which salient features trigger the regional identification. In a second step, the speech samples are analyzed by the variables 'pleasantness' and 'correctness' defined by Dennis R. Preston. The central question here is: Are speech samples with a high pleasure value also automatically considered correct? Finally, an interpretation of metalinguistic comments in the speech examples will give more insight into folk linguistic concepts and the role of salient features in this regard.